The Impact of Banning Female Education on Household Income in Afghanistan - Hafizi, Ziyada (International Journal Administration, Business & Organization, 2025)
This study explains how the ban on girls’ education in Afghanistan after August 2021 has affected family income. For many years, girls’ education helped families because educated women had better chances to find jobs and bring in steady earnings. When schools and universities closed again, many families worried about how they would manage without the future income they expected from their daughters. The purpose of this study is to measure how the ban has changed household income. A quantitative survey was carried out with 316 households in Kabul, Herat, Balkh, and Badakhshan. Data were collected through an online questionnaire, and the analysis used Partial Least Squares Structural Equation Modeling to examine the links between female education, expectation loss, support for education, and income. The findings show that the education ban has clearly reduced household income and increased financial stress. Families who had daughters with higher levels of education before the ban reported even bigger income losses. Expectation loss also played a role, as households that relied on future income from their daughters experienced stronger financial decline. Even with these difficulties, most families still support girls’ return to school. Overall, the results show that stopping girls from studying directly harms family finances and increases economic problems for communities across Afghanistan.